Activation of multiple genes by provirus integration in the Mlvi-4 locus in T-cell lymphomas induced by Moloney murine leukemia virus. - Tsichlis, P N (1990)
Moloney murine leukemia virus-induced rat T-cell lymphomas harbor proviruses integrated near c-myc and near Mlvi-1/Mis-1/Pvt-1, another locus of common integration which maps 270 kilobases 3' of c-myc. In this report, we present the characterization of a new locus of common integration in Moloney murine leukemia virus-induced T-cell lymphomas (Mlvi-4) which maps 30 kilobases 3' of c-myc, between c-myc and Mlvi-1. The Mlvi-4 locus, whose chromosomal map location is conserved in rats, mice, and humans, is also the target of chromosomal rearrangements in a variety of animal and human tumors. Evidence presented elsewhere shows that provirus integration in Mlvi-4 enhances the expression of c-myc and Mlvi-1 by cis-acting mechanisms operating over long distances of genomic DNA. In this manuscript, we show that provirus integration in the Mlvi-4 locus activates, by promoter insertion, one additional gene which maps immediately 3' to the cluster of the Mlvi-4 proviruses and which is transcribed in the same orientation as c-myc, giving rise to 3- and 10-kilobase mRNA transcripts. The Mlvi-4 gene is also expressed in normal thymus and spleen at very low levels, giving rise to 3- and 5.5-kilobase messages. Although Mlvi-4 is expressed in normal thymus, it is not expressed in Moloney murine leukemia virus-induced T-cell lymphomas corresponding to several stages of T-cell differentiation, but lacking a provirus in this locus. This suggests that Mlvi-4 may be expressed only in a subpopulation of T cells. We conclude that provirus insertion in Mlvi-4 activates c-myc and two additional genes, Mlvi-1 and Mlvi-4, whose expression is restricted to, and may be developmentally regulated in, T cells. Since Mlvi-4 is the target of genetic changes in a great variety of human and animal neoplasms, these results are critical for our understanding of oncogenesis.